Licensing Policy Regarding the Suitability of Space Utilization Activities for Micro and Small Enterprises in Buleleng Regency - AGUSTINA, I Kadek Raos A; MAHENDRAWATI, Ni Luh; JAYA , I Wayan Kartika (Protection: Journal Of Land And Environmental Law, 2025)
This study aims to examine the spatial utilization activity suitability licensing (KKPR) policy for Micro and Small Enterprises (MSEs) in Buleleng Regency, particularly in the context of the manual implementation of the Spatial Utilization Activity Suitability Approval (PKKPR). The main focus of the study is to assess the extent to which this policy has guaranteed the principles of legal certainty, justice, and benefit for business actors, as mandated by the Job Creation Law and Government Regulation Number 21 of 2021. The research method used is an empirical legal research method that examines the gap between legal regulations and the reality in society using a juridical analysis approach supported by primary data sourced from interviews, which are then analyzed qualitatively and processed with legal theories. The results of the study indicate that the implementation of the manual policy by the Buleleng Regency Government is still not in line with the principle of risk-based licensing simplification through OSS-RBA. This policy, although intended to protect MSEs from spatial planning violations, actually creates procedural inconsistencies and additional administrative burdens that have the potential to reduce legal certainty and the efficiency of public services. This study recommends accelerating the digitalization of RDTR, integrating the regional licensing system with OSS-RBA, and strengthening education and coaching for MSMEs so that the spatial licensing process can be implemented fairly, beneficially, and provide optimal legal certainty.